Temporal Contiguity Training Influences Behavioral and Neural Measures of Viewpoint Tolerance - Van Meel, Chayenne; Op de Beeck, Hans P. (Frontiers in Human Neuroscience, 2018)
Humans can often recognize faces across viewpoints despite the large changes in low-level image properties a shift in viewpoint introduces. We present a behavioral and an fMRI adaptation experiment to investigate whether this viewpoint tolerance is reflected in the neural visual system and whether it can be manipulated through training. Participants saw training sequences of face images creating the appearance of a rotating head. Half of the sequences showed faces undergoing veridical changes in appearance across the rotation (non-morph condition). The other half were non-veridical: during rotation, the face simultaneously morphed into another face. This procedure should successfully associate frontal face views with side views of the same or a different identity, and, according to the temporal contiguity hypothesis, thus enhance viewpoint tolerance in the non-morph condition and/or break tolerance in the morph condition. Performance on the same/different task in the behavioral experiment (N = 20) was affected by training. There was a significant interaction between training (associated/not associated) and identity (same/different), mostly reflecting a higher confusion of different identities when they were associated during training. In the fMRI study (N = 20), fMRI adaptation effects were found for same-viewpoint images of untrained faces, but no adaptation for untrained faces was present across viewpoints. Only trained faces which were not morphed during training elicited a slight adaptation across viewpoints in face-selective regions. However, both in the behavioral and in the neural data the effects were small and weak from a statistical point of view. Overall, we conclude that the findings are not inconsistent with the proposal that temporal contiguity can influence viewpoint tolerance, with more evidence for tolerance when faces are not morphed during training.